2017
DOI: 10.1177/1177271917695832
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biomarker Panel to Identify Steroid Resistance in Childhood Idiopathic Nephrotic Syndrome

Abstract: Idiopathic nephrotic syndrome (NS) is the most common glomerular disorder of childhood. Response to initial treatment with corticosteroids is an indicator of prognosis, as resistant patients often present more progressive disease. In this cross-sectional pilot study, we set out to discover a panel of noninvasive biomarkers that could distinguish steroid-resistant nephrotic syndrome (SRNS) from steroid-sensitive nephrotic syndrome (SSNS). Information gleaned from such a panel could yield more individualized tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…podocyte actin cytoskeleton, 29 and to distinguish SRNS via a urine proteomics approach, although it was not identified as a candidate on validation by enzymelinked immunosorbent assay (ELISA). 16 Our studies showed that HPX could discriminate patients with SSNS versus SRNS pretreatment, and that steroid treatment significantly increased plasma HPX levels in SSNS (but not SRNS) patients.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…podocyte actin cytoskeleton, 29 and to distinguish SRNS via a urine proteomics approach, although it was not identified as a candidate on validation by enzymelinked immunosorbent assay (ELISA). 16 Our studies showed that HPX could discriminate patients with SSNS versus SRNS pretreatment, and that steroid treatment significantly increased plasma HPX levels in SSNS (but not SRNS) patients.…”
Section: Resultsmentioning
confidence: 56%
“…17,[21][22][23][24][25][26] More recently, proteomic profiling of patients with NS based on their histology and clinical phenotype has yielded a panel of proteins able to distinguish between these different groups. 16,17 These studies had important differences from the current study. First, both of these studies analyzed urine samples.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations